Metallo-β-lactamases and a tug-of-war for the available zinc at the host–pathogen interface - Bahr, Guillermo (2022)
Fil: Fil: Bahr, Guillermo. Instituto de Biología Molecular y Celular de Rosario (IBR-CONICET); Argentina.